First-Principles Study of Metal Impurities in Silicon Carbide: Structural, Magnetic, and Electronic Properties - Zhang, Lin; Cui, Zhen (Frontiers in Materials, 2022)
The configurations of ten types of metal-doped silicon carbide (SiC) systems were investigated by first-principles calculations. The dopants includes eight types of 3d series transition metal atoms, one semi-metal Ge atom, and one other-metal Al atom. For all metal-doped SiC systems, the steadiest doping sites are fixed at the substituted Si site, while the Ti-SiC system exhibits the most potent binding. The properties of these new systems vary with the doping atoms. The Sc-, and Al-SiC system convert to magnetic metals. The Ti- and Ge-SiC remain non-magnetic semiconductors, while the V-, Cr-, Mn-, Fe-, Co-, and Zn-SiC systems turn into magnetic semiconductors with magnetic moments related to the valence electron number of dopants. Partial charge transfers from the metal atoms to the adjacent C atoms, accompanying the change in electron-emitting capacity of the new systems. The work function achieves the minimum of 3.439 eV in the Co-SiC system, just 71.6% of the original SiC system. Our analysis indicates that the potent binding energy of the Ti-SiC system is due to the complete bonding states between the transition metal Ti and the adjacent C atoms. The magnetism evolution in semiconducting metal-doped SiC is attributed to the occupation mode of the hybridization orbitals nearby the Fermi level, which are determined by the coupling of 3d orbital of TM atoms and the defect states of the vacancy atoms. The adjustable magnetic and eletronic properties of metal-doped SiC systems provide a flexible method in designing more suitable SiC-based spintronics and field electron-emitting devices.